1966
DOI: 10.1007/bf01338655
|View full text |Cite
|
Sign up to set email alerts
|

Die Entwicklung der Elektronenlawine in den Plasmakanal, untersucht mit Bildverst�rker und Wischverschlu�

Abstract: The application of high gain image intensifier and image converter streak shutter techniques to investigations of faintly luminous early stages of gaseous discharges discloses in some detail the development of electron avalanches into anode-and cathode-directed streamers as soon as the critical amplification (n~ l0 s) is attained in the gap. The velocities of both of the streamer branches were measured quantitatively as to the dependence on pressure (p)*, field (E/p) and gas (Nitrogen and various mixtures), ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
33
0
1

Year Published

1968
1968
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(34 citation statements)
references
References 0 publications
0
33
0
1
Order By: Relevance
“…The enhanced and accelerated streamer stage was observed in both directions; the significantly fast and steep ionization waves were found to start at the cathode as well as at the anode on arrival of the respective streamers. The measured velocities were up to 10 mm/ns [8], [9]. In addition, the emission from positive pulsed streamer discharges in air at atmospheric pressure was observed with an intensified charge-coupled device camera with a high-speed gate in previous work in which the streamer propagation process and its propagation velocity in a coaxial electrode were reported [11].…”
Section: Introductionmentioning
confidence: 84%
“…The enhanced and accelerated streamer stage was observed in both directions; the significantly fast and steep ionization waves were found to start at the cathode as well as at the anode on arrival of the respective streamers. The measured velocities were up to 10 mm/ns [8], [9]. In addition, the emission from positive pulsed streamer discharges in air at atmospheric pressure was observed with an intensified charge-coupled device camera with a high-speed gate in previous work in which the streamer propagation process and its propagation velocity in a coaxial electrode were reported [11].…”
Section: Introductionmentioning
confidence: 84%
“…The negative streamer advances in a diffusive and selfchoking manner, making propagation into the lower-field region away from the point source relatively difficult. Wagner [1966] found that fields of 3 X 10 • v m -• or more are necessary for long-range propagation of negative streamers formed in the middle of a uniform-field gap. However, the details of the positive streamer results provide us with some important insight regarding the physics controlling their propagation.…”
Section: D•scuss•o•mentioning
confidence: 98%
“…At voltages close to the minimum breakdown potential the spark channel has been shown to develop from the constriction of the diffuse glow discharge formed from the superposition of many generations of electron avalanches (Cavenor and Meyer 1969). At large overvoltages, however, single avalanches have been observed to develop into luminous conducting filaments, called streamers, which completely bridge the electrode gap within the transit time of the initial avalanche (Wagner 1966).The criterion proposed for the occurrence of this streamer mode of development is that the charge carrier number in the initial avalanche should attain a value of some lO9 ions and electrons and that the electrons be concentrated within the diffusion radius of the avalanche. Under such conditions it is suggested that enhancement of the electric field by the space charge, in the vicinity of the avalanche, is sufficient to allow gas ionizing radiation to extend the ionized region simultaneously towards both electrodes (Raether 1964).…”
mentioning
confidence: 99%
“…At voltages close to the minimum breakdown potential the spark channel has been shown to develop from the constriction of the diffuse glow discharge formed from the superposition of many generations of electron avalanches (Cavenor and Meyer 1969). At large overvoltages, however, single avalanches have been observed to develop into luminous conducting filaments, called streamers, which completely bridge the electrode gap within the transit time of the initial avalanche (Wagner 1966).…”
mentioning
confidence: 99%